Enhancing deteriorated heat transfer of supercritical nitrogen in a vertical tube with wire matrix insert. (December 2020) - Wang, Yi; Lu, Tiejun; Drögemüller, Peter; Yu, Qinghua; Ding, Yulong; Li, Yongliang
Highlights: The convective heat transfer of supercritical nitrogen in a vertical straight tube can be improved by adding wire matrix insert. The addition of wire matrix insert may enhance turbulent mixing in the straight tube, especially beneficial for the buoyancy dominated region. An energy efficiency evaluation reveals that there might exist an optimum operating condition leading to the best convective heat transfer performance of supercritical nitrogen in a straight tube with wire matrix insert. A heat transfer correlation is needed exclusively for in-tube convective heat transfer of supercritical nitrogen. Abstract: In this study, hiTRAN TM wire matrix tube insert was used to improve the heat transfer deterioration of supercritical nitrogen (N2 ) in a heated tube caused by the effects of thermo-physical property variations and buoyancy force. Heat transfer experiments were carried out with N2 flowing upwardly in a vertical circular tube with and without the wire matrix insert under a sequence of experimental conditions including pressures of 35 and 40 bar, mass flow rate of 27.6 and 41.3 g/min and constant heat flux conditions at 6.8, 8.0 and 9.3 kW/m 2, respectively. Experimental results show that N2 exhibits similar heat transfer behavior when transiting across the pseudo-critical point as other fluids such as water and CO2 . Due to the addition of the wire matrix insert, that intensified the overall fluid mixing in the test tube, the heat transfer performance of N2 was enhanced by more than 42% and up to 2.35 times while the pressure drop increase was negligible compared to the system inlet pressure. Moreover, it has been demonstrated that there might exist an optimum combination of experimental conditions leading to the maximum performance of the wire matrix insert. Furthermore, as the results show, with the Dittus-Boelter correlation and correlations for water and CO2 falling short of fitting the heat transfer data of N2, a heat transfer correlation, exclusively for N2 going through the pseudo-critical point is needed. The findings in this study also reveal that both supercritical N2 internal flow heat transfer and the use of wire matrix insert to enhance the deteriorated heat transfer of supercritical fluids are promising topics and require more significant attentions in future studies.